2016
DOI: 10.3892/ol.2016.5509
|View full text |Cite
|
Sign up to set email alerts
|

Pinus massoniana bark extract inhibits migration of the lung cancer A549 cell line

Abstract: Abstract. The bark of Pinus massoniana is a traditionalChinese medicine for the treatment of various health disorders. Previous studies have demonstrated that P. massoniana bark extract (PMBE) may induce the apoptosis of hepatoma and cervical cancer cells. However, whether PMBE is able to inhibit the migration of lung cancer cells requires further investigation. In the current study, the effects of PMBE on the viability of human lung cancer A549 cells were detected using an MTT assay. The migration of lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For that three different cell lines, one normal mouse cell line (L929) and two human cell lines (normal-HEK293T-and derived from cancer tissue-A549) were used. Several authors have used similar cell lines to evaluate the potential toxicity of other plant extracts and isolated products [56,57]. Different concentrations of active extracts were placed in contact with the cells and their ability to metabolize resazurin into resorufin in the presence of PBE was used as a measurement of cells metabolic activity.…”
Section: Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For that three different cell lines, one normal mouse cell line (L929) and two human cell lines (normal-HEK293T-and derived from cancer tissue-A549) were used. Several authors have used similar cell lines to evaluate the potential toxicity of other plant extracts and isolated products [56,57]. Different concentrations of active extracts were placed in contact with the cells and their ability to metabolize resazurin into resorufin in the presence of PBE was used as a measurement of cells metabolic activity.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…Touriño and collaborators [60] reported that P. pinaster bark extracts have a high antioxidant activity and can control proliferation in a human melanoma cell line. Additionally, Mao et al [57] demonstrated that extracts from the Pinus massoniana bark inhibit migration of the lung cancer A549 cell line.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…The samples were analyzed using a FACScan flow cytometer. On the basis of DNA content, the percentage of cells in each stage in the cell cycle (G 1 , S, and G 2 /M) was calculated using ModFit Lt. 3.0 s [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…PMBE was demonstrated to exhibit various bioactivities such as antiviral, anti-allergic, antioxidant and anticancer [2,7,8] . It has been proven that PMBE mainly induces cancer cells cycle arrest at S and G2/M phase [9] , further induces apoptosis of cancer cells via mitochondrial pathway and / or death receptor pathway [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%